Hematological Profile of Silver Pompano (Trachinotus blochii) Broodstock with Hormonal Induction and Phytobiotic Supplementation in Feed - Azizah Azizah; Munti Sarida; Yudha Trinoegraha Adiputra; Gregorius Nugroho Susanto; Agus Setyawan (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
This study evaluates the hematological profile of potential broodstock silver pompano (Trachinotus blochii) through hormonal induction and phyto-biotic supplementation via feed. An experimental trial was conducted for 30 days to assess the hematological profile of potential broodstock Trachinotus blochii. This study employed a completely randomized design (CRD) in two research experiments. The first experiment utilized hormonal induction with estradiol-17β hormone on female silver pompano broodstock, consisting of 3 treatments: E1 (0 mg/kg), E2 (20 mg/kg), and E3 (60 mg/kg), whereas the second experiment employed phyto-biotic induction using Tribulus terrestris extract (ETT) and gonadotropin hormone, consisting of 5 treatments: T1: ETT 0 mg/kg feed, T2: ETT 50 mg/kg feed, T3: ETT 250 mg/kg feed, T4: ETT 50 mg/kg feed + gonadotropin 1000 IU/kg body weight, and T5: ETT 250 mg/kg feed + gonadotropin 500 IU/kg body weight, both experiments used 8 individuals as replicate per treatment. The results of the study indicated that all major hematological indices such as total erythrocytes, total leukocytes, and hematocrit levels were higher in male silver pompano broodstock supplemented with Tribulus terrestris extract compared to female silver pompano broodstock induced hormonally with estradiol-17β hormone.